CHALLENGES OF INCLUSIVE EDUCATION (Conferencea, 2024)
Our school happily accepted the challenge to introduce inclusive education.At the Pedagogical Council, we discussed the difficulties that may accompany this process. We formulated them, identified key issues, and identified ways to eliminate them.The introduction of inclusive education showed several directions of the need to transform the school environment; In order to determine the physical environment, educational process, resources, community relations and the needs of teachers and students.